Addiction psychiatry and nursing: emerging research and the evolving roles of nurses - P. Vanaja; Rehana Banoo; Kalaiselvi Xavier A.; Neeraj; Ushakiran Thirunavukarasu; Mayanglambam Sankerdev Singh; S. Tamilselvi; Gattu Pavithra; Ulluri Naga Srilakshmi; P. Emmanuel Raju; Trilok Chand Sharma; Mohammed Umar (International Journal of Research in Medical Sciences, 2026)
Substance use disorders (SUDs) represent a major global public health challenge associated with significant morbidity, mortality, psychiatric comorbidity, social disruption, and economic burden. Addiction psychiatry has evolved considerably over the past decade through advances in neurobiology, psychopharmacology, digital health, precision medicine, and integrated behavioral healthcare models. Concurrently, the role of nurses in addiction psychiatry has expanded beyond traditional bedside care to encompass prevention, screening, harm reduction, treatment coordination, psychotherapy, medication-assisted treatment (MAT) support, recovery-oriented care, research, leadership, and policy advocacy. Emerging evidence demonstrates that nurses are central to improving outcomes among individuals with SUDs, particularly in integrated mental health settings. Contemporary addiction nursing emphasizes person-centered care, trauma-informed approaches, stigma reduction, motivational interviewing, relapse prevention, and community engagement. This review examines current developments in addiction psychiatry and explores the evolving responsibilities of nurses across clinical, educational, research, and policy domains. The review synthesizes evidence from peer-reviewed literature published between 2019 and 2026, highlighting innovations, challenges, and future directions in addiction nursing practice. Findings indicate that advanced psychiatric nurses are increasingly involved in comprehensive assessment, integrated treatment planning, harm reduction initiatives, and management of dual diagnoses. Despite substantial progress, barriers such as workforce shortages, inadequate education, stigma, fragmented services, and limited policy support continue to impede optimal care delivery. Strengthening addiction-focused nursing education, expanding advanced practice roles, promoting interprofessional collaboration, and supporting evidence-based practice are critical for addressing the growing burden of SUDs.